Sox9 Expression in Amniotes: Species-Specific Differences in the Formation of Digits - Montero, Juan A.; Lorda-Diez, Carlos I.; Francisco-Morcillo, Javier; Chimal-Monroy, Jesus; Garcia-Porrero, Juan A.; Hurle, Juan M. (Frontiers in Cell and Developmental Biology, 2017)
In tetrapods the digit pattern has evolved to adapt to distinct locomotive strategies. The number of digits varies between species or even between hindlimb and forelimb within the same species. These facts illustrate the plasticity of embryonic limb autopods. Sox9 is a precocious marker of skeletal differentiation of limb mesenchymal cells. Its pattern of expression in the developing limb has been widely studied and reflects the activity of signaling cascades responsible for skeletogenesis. In this assay we stress previously overlooked differences in the pattern of expression of Sox9 in limbs of avian, mouse and turtle embryos which may reflect signaling differences associated with distinct limb skeletal morphologies observed in these species. Furthermore, we show that Sox9 gene expression is higher and maintained in the interdigital region in species with webbed digits in comparison with free digit animals.